ANALISIS PROBLEMATIKA ZAKAT PADA BAZNAS KOTA TASIKMALAYA:PENDEKATAN METODE ANALYTIC NETWORK PROCESS (ANP) - Firmansyah, Irman; Sukmana, Wawan (Jurnal Riset Akuntansi dan Keuangan, 2014)
Zakat is an obligation that must be carried out by muzakki that not only aims to carry out obligations to Almighty but sharp-edged nature of social justice among mankind. Therefore charity must be managed properly by the board amilin especially by channeling zakat use specifically targeted at Tasikmalaya City Baznas charity board.The study was to examine the affairs of Baznas perzakatan at Tasikmalaya City. Analysis tool used namely Analysis Network Process (ANP) is a qualitative-quantitative method using super decision software . The analysis showed that there is an internal problem which consists of lacking leadership and lacking performance OPZ performance. The problems consist of the absence of external PERDA about channeling zakat institutions and communities less know Baznas. As for an internal solution consisting of leadership and performance maximization of transparency and distribution, while the external solution consisted of socialization and support Baznas scholars. Kendall coefficient ( W ) ranged from 0.970 to 0.9975 means that all respondents have the same relative answer.